Knowledge, attitude and practice scale of medical personnel on smoking cessation guidelines: a review on associations and questionnaires - Shalihin, Mohd Shaiful Ehsan; Nik Mohamed, Mohamad Haniki (Universiti Malaysia Sabah, 2019)
The number of active smokers in Malaysia is increasing despite the availability of stop smoking clinics and smoking cessation medications. Other than smokers’ level of motivation to quit smoking, competency of the healthcare professionals involved in providing smoking cessation intervention using evidencebased guidelines needs to be considered. Hence, knowledge, attitude and practice (KAP) of the healthcare providers in relation to existing clinical practice guidelines on smoking cessation should be assessed. In this review, we look at the factors contributing to the KAP of medical personnel on the guidelines and also the previously available assessment tool, mainly in the form of a validated questionnaire, for the purpose of applying it to the context of the Malaysian healthcare providers.